Aplicación de las medidas de bioseguridad en el manejo de plaguicidas por los agricultores del barrio Pindo Mirador de Mera – Pastaza. Año 2015. - Haro Naveda, Maricela Johanna (2016)
This research was aimed at determining the application of biosecurity measures in handling pesticides by farmers in the neighborhood Pindo Mirador del Mera Canton. Its design was: transversal, descriptive, bibliographic, field. Techniques of observation and the survey was applied to 30 farmers was used. As a result it was found that 23.33% are 60 or older; in 50.01% between the ages of 20 and 49 years and 13.33% they are teenagers and 50 to 59 years equally. With 73.33% predominance in males; ethnic mestizo 90%; been married in a civil 53.33%; cohabiting at 13.33%. Instruction is primary in 73.33%. The level of use of protective clothing is low at 60% higher default use coveralls at 93.33%. Regarding the use of protective clothing the following was found: 60% use gloves: coveralls there is a breach of 93.33%; 93.33% boots used; mask 66.67% do not use it; They do not use helmet 76.67% and breach of glasses is 100%. The level of compliance with other biosecurity measures is medium in 73.33% and prevalent are: uses the same work clothes without washing in 76.67%; breach of bath full in 73.33%. The factors influencing failure are 33.33% believe it is not important; ignorance at 26.67%. It was concluded that the level of implementation of biosecurity measures is low at 60.00%; the main causes of failure are ignorance in 43.34% and minor in 33.33%. As nursing plan educational activities, educational manual and triptych, demonstration workshops was held Keywords: Application; Biosecurity Measures; Pesticides; Farmer